Correlation of a dynamic model for immunological synapse formation with effector functions: two pathways to synapse formation. - Lee, S; Hori, Y; Groves, J; Dustin, M; Chakraborty, A (2002)
During antigen recognition by T cells different receptors and ligands form a pattern in the intercellular junction called the immunological synapse, which might be involved in T-cell activation. Recently, a synapse assembly model has been proposed, which enables the calculation of the propensity for synapse assembly driven by membrane-constrained protein binding interactions. We bring together model predictions of mature synapse assembly with data on the dependence of T-cell responses on T-cell receptor (TCR)-MHC-peptide (pMHC) binding kinetics. Predictions of mature synapse assembly, based on TCR-pMHC binding kinetics, correlate well with observed cytokine responses by T cells bearing the relevant TCR but not with cytotoxic T lymphocyte-mediated killing. We discuss the suggested different role for the synapse in pre- and post-nuclear activation events in T cells. The view of immunological synapse assembly given here emphasizes the importance of both the on and off rates for the TCR-pMHC interaction and in this context recent data on a positive role for analogs of self-peptides in synapse assembly is considered.